Gastroprotective Effect of Chinese Cabbage (Brassica oleracea L. var. pekinensis) Juice in Sprague Dawley Rats - Chin, Jin H.; Wong, Kah Hui; Yeong, Soh Onn (Natural Products Journal, The, 2020)
Background: Chinese cabbage or Brassica oleracea L. var. pekinensis is an edible leafy green vegetable in the family of Brassicaceae. Ethnopharmacological studies have shown that the juice of cabbage leaves is commonly used in the treatment of gastrointestinal disorders, irritable bowel syndrome, minor cuts and wounds and mastitis. Objective: This study was aimed to examine the gastroprotective effect of Chinese cabbage (Family: Brassicaceae) juice in rats by using ethanol-induced gastric ulcer model. Methods: Thirty albino male Sprague Dawley rats (150 ± 20 g) were divided into 6 groups with five rats (n = 5) in each group. The normal control group was treated with distilled water while the positive control group was intragastrically administered with omeprazole (20 mg/kg). Cabbage juice at 500 mg/kg was given orally to three experimental groups for 1-day, 7-day and 14-day, respectively. Ethanol (70 % v/v) was orally treated to all rats one hour after the last dose treatment except the normal control group. Results: Results obtained showed that repeated consumption of cabbage juice for 7 days and 14 days exhibited an increase in accumulation mucus and in the levels of superoxide dismutase (SOD), glutathione- s-transferase (GST) and glutathione peroxidase (GSH-Px) as well as a reduction in gastric lesion area induced by ethanol compared with the ulceration control group. Conclusion: In conclusion, the gastroprotective effect of Chinese cabbage juice could be associated with its ability to increase endogenous antioxidant activities of SOD, GST and GSH-Px and mucus secretion in rat stomach.
Keywords: glutathione